Information needs on breast cancer genetic and non-genetic risk factors in relatives of women with a BRCA1/2 or PALB2 pathogenic variant. (December 2021) - Brédart, Anne; De Pauw, Antoine; Anota, Amélie; Tüchler, Anja; Dick, Julia; Müller, Anita; Kop, Jean-Luc; Rhiem, Kerstin; Schmutzler, Rita; Devilee, Peter; Stoppa-Lyonnet, Dominique; Dolbeault, Sylvie
Abstract: Objectives: Comprehensive breast cancer (BC) risk models integrating effects of genetic (GRF) and non-genetic risk factors (NGRF) may refine BC prevention recommendations. We explored the perceived information received on BC risk factors, and related characteristics, in female relatives of women with a BRCA1/2 or PALB2 pathogenic variant, undergoing BC risk assessment using the CanRisk© prediction tool. Methods: Of 200 consecutive cancer-free women approached after the initial genetic consultation, 161 (80.5%) filled in questionnaires on their perception of information received and wished further information on BC risk factors (e.g., being a carrier of a moderate risk altered gene, personal genetic profile, lifestyles). Multilevel multivariate linear models were performed accounting for the clinician who met the counselee and exploring the effect of counselees' socio-demographic, familial and psychological characteristics on the perceived extent of information received. Results: Perceived no/little information received and wish for further information were more frequent for NGRF (>50%) than for GRF, especially high-risk genes (<20%). Perceived amount of information received and desire for further information were inversely correlated (p=<0.0001). Higher education level related to lower perceived levels of information received on GRF. Younger counselees' age (β = 0.13, p = 0.02) and less frequent engagement coping (e.g., inclination to solicit information) (β = 0.24, p = 0.02) related to lower perceived information received about NGRF. Other assessed counselees' features were not found to be associated to GRF and NGRF information perception. Conclusions: Awareness of counselees' perceived lack of information on BC risk factors indicates a need to enhance evidence-based information on BC NGRF especially. Highlights: Comprehensive breast cancer (BC) risk assessment may integrate genetic and non-genetic risk factors, providing more accurate BC risk estimates and nuanced clinical recommendations. Standard BC genetic counseling focuses on major genetic risks. Female relatives of women with a BRCA1/2 or PALB2 pathogenic variant perceived a lack of information about non-genetic risk factors. As these factors may affect health prevention, enhancing the provision of information about them appears necessary. Further research should focus on modalities of information delivery about overall BC risk factors such as by which health care professionals provide this information and at which time-point in the BC risk counseling journey.